(untitled) (Fiep Bulletin - online, 2012)
The objective of this study was to develop a model of classroom practice, using two different execution speeds protocols of movement to monitor the possible changes that the acute specific protocol could generate the following variables: maximal strength (1RM), standing horizontal jump (SHJ) and thigh circumference (TC) of individuals beginners to exercise against resistance, before and after protocol classified as a fast and slow execution of movement in the concentric-eccentric cycles. The sample consisted of four healthy female volunteers, students of Physical Education at the South Minas Gerais Federal Institute of Education, Science and Technology campus Muzambinho/MG, with a low level of strength training. The sample was divided into two groups, the first, individuals aged 19±0.00 years old, called the Fast Execution Group (FEG), mechanical actions performed with a time of 1.5 sec. for each repetition, and the other 2 subjects aged 23.50±0.71 years old, called Slow Execution Group (SEG), carried out such actions with 6 sec. by repetition. The tests used were: metronome (Crystal), leg press 90° and leg extension chair (Physicus), anthropometric tape to check the TC (Sanny), measuring tape to check the SHJ (Western), weight scale to total body mass (Tanita) and a height scale (Filizola). With the SEG TC results (0 hours = 2.03%, 0.78 s% = 24 hours, 48 hours = 0.10%) and FEG (0 hours = 1.36%, 0.31 s% = 24 hours, 48 hours = 0 10%), it was observed that the training protocol executions generated most of the SEG response falls in the percentage 1RM tests, and increased SHJ and TC. Therefore, we can say that the results of this study, the training leads to higher SEG micro muscle damage, thus increasing the TC and a drop in 1RM tests and SHJ, compared to training with the FEG, however, these results may be found due the small number of women, coupled with little experience in weight lifting.